Análise da atividade em um Centro de Atenção Psicossocial - Gonzaga, Pamela de Sousa (2015)
The Psychiatric Reform aims to break the isolation pinelian, seeking the crietion of possibilities, the production of sociability and subjectivities, allowing the subject of the experience of madness, who has been denied the world of citizenship, to become in fact a subject and not object of knowledge. It is this process of transformation that workers in the mental health area are immersed, although there is progress, there are also challenges that must be overcome. Therefore, this study aimed to analyze the work situations at CAPS III in Campina Grande - PB in light of the Psychiatric Reform. For this, this research has descriptive, cross-sectional and exploratory design, with a survey data and qualitative approach. The survey was conducted in 2013 at CAPS III in Campina Grande - PB. The study gathered 15 professionals that make up the team at the refered CAPS that consented to participation. We use as an analytical perspective the framework of ergology. We conclude that the work activity of these professionals is marked by unpredictability, demanding an exaggerated use of themselves and shown as exhausting. Among the challenges encountered in daily life of this unit we highlight the precariousness of employment, difficulties with the resources, the physical structure and relations with the municipal health network. As a coping strategy, team meetings is presented as favorable spaces for expression and debate that act as a support mechanism, reducing the wear caused by the activity.